May Salivary Alpha-Amylase Level Be a Useful Tool for Assessment of the Severity of Schizophrenia and Evaluation of Therapy? A Case Report. (30th September 2012) - Ieda, Masa; Miyaoka, Tsuyoshi; Kawano, Kiminori; Wake, Rei; Inagaki, Takuji; Horiguchi, Jun
Abstract : Background . Previous studies suggested dysfunction of the autonomic nervous system (ANS) in schizophrenia patients, but the mechanism remains unclear. Recently, the measurement of salivary alpha-amylase (sAA) has been considered a useful tool for evaluating ANS, especially the sympathoadrenal medullary system. Furthermore, there was a report that patients with schizophrenia showed much higher sAA level than normal controls. Methods . We present the case of a 51-year-old female with catatonic schizophrenia. She needed the treatment of electroconvulsive therapy (ECT). We evaluated her sAA level and her psychiatric symptoms during the treatment. Results . Before ECT treatment, she showed high sAA level. Her sAA level decreased during the course of ECT, and this attenuation was accompanied by improvement of schizophrenic symptoms. Conclusion . We consider that measurement of the sAA level may be one of the useful biological markers for assessment of psychotic state and efficacy of treatment in patients with schizophrenia.